Triglyceride-cholesterol-body weight index associated with the risk of metabolic dysfunction-associated steatotic liver disease: a population-based cross-sectional study - Fan, Li; Su, Yongkang; Chen, Yue; Xu, Ling; Huang, Hairong; Lu, Chunsheng; Peng, Jia; Sun, Yingbin; Jia, Min (Frontiers in Nutrition, 2025)
BackgroundThe triglyceride-cholesterol-body weight index (TCBI), a novel parameter integrating serum triglycerides (TG), total cholesterol (TC), and body weight (BW), has not been comprehensively investigated in relation to metabolic dysfunction-associated steatotic liver disease (MASLD). This study aimed to examine the association between TCBI and MASLD.MethodsThis cross-sectional study used data from the NAGALA project in Japan, including 14,242 participants. TCBI was calculated using the formula: TG (mg/dL) × TC (mg/dL) × BW (kg)/1,000. Participants were stratified into quartiles based on natural log-transformed TCBI (TCBI-LN). The association between TCBI and MASLD was assessed using multiple logistic regression, restricted cubic splines (RCS), subgroup analyses, and receiver operating characteristic (ROC) curve analysis.ResultsAmong the 14,242 participants, the mean age was 43.53 ± 8.89 years, and 48.03% were female. In the fully adjusted model, each 1-unit increase in TCBI-LN was associated with a 1.69-fold increased risk of MASLD (OR = 2.69, 95% CI: 2.00–3.64, P < 0.001). Compared to quartile 1, participants in quartile 4 of TCBI-LN had a 2.91-fold higher risk of MASLD (OR = 2.91, 95% CI: 1.94–4.35, P < 0.001). Trend analysis and RCS curve fitting revealed a positive linear and dose-response relationship between TCBI and MASLD risk. Subgroup analysis showed that TCBI was a stronger predictor of MASLD in individuals with abnormal body mass index (BMI) or normal waist circumference (WC). ROC analysis indicated that TCBI had good predictive performance for MASLD among individuals with normal BMI (AUC = 0.810, 95% CI: 0.801–0.822).ConclusionTriglyceride-cholesterol-body weight index showed a significant linear positive association with MASLD risk, particularly in individuals with abnormal BMI or normal WC. Moreover, TCBI demonstrated strong predictive accuracy for MASLD among individuals with normal BMI.